FORECASTING DENGAN METODE REGRESI LINIER PADA SISTEM PENUNJANG KEPUTUSAN UNTUK MEMPREDIKSI JUMLAH PENJUALAN BATIK (STUDI KASUS KUB SARWO ENDAH BATIK TULIS LASEM) - Tutik Khotimah; Ratih Nindyasari (Jurnal Mantik Penusa, 2017)
Almost region in Indonesia produces Batik. One of the region is Lasem which popular with Batik Lasem that own characteristics. KUB Sarwo Endah is the Business Group in Lasem have still active in Batik Business. The problem occurred when KUB Sarwo Endah had a target to expand marketing field in order to increase KUB revenue. In addition, the KUB also has difficulty in predicting the number of sales, going forward, which will have an impact on the amount of KUB revenue, the number of workers and the level of demand. The Linear Regression method is used to calculate the predicted number of sales. Furthermore, the results of this forecasting will be used as input values to support a decision precisely in the Decision Support System (SPK) which will help KUB managers when it will expand its business sector. The results of the study obtained that by using the data on the number of sales in the previous period, it can be obtained the results of the prediction of the number of sales for the period or the future. Keywords: Forecasting, number of sales, Decision Support System, Batik Lasem